2001
DOI: 10.1089/104454701753342758
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NASA Light-Emitting Diode Irradiation on Wound Healing

Abstract: Objective: The purpose of this study was to assess the effects of hyperbaric oxygen (HBO) and near-infrared light therapy on wound healing. Background Data: Light-emitting diodes (LED), originally developed for NASA plant growth experiments in space show promise for delivering light deep into tissues of the body to promote wound healing and human tissue growth. In this paper, we review and present our new data of LED treatment on cells grown in culture, on ischemic and diabetic wounds in rat models, and on acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
291
1
23

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 435 publications
(327 citation statements)
references
References 31 publications
7
291
1
23
Order By: Relevance
“…In the same study, comparison between LED light and laser light revealed that both illumination systems promoted an increase in fibroblast proliferation, confirming that LED light can be used as a substitute for the laser. Other in vitro studies have also found that light irradiation stimulates proliferation of different cell lines [14,[17][18][19].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…In the same study, comparison between LED light and laser light revealed that both illumination systems promoted an increase in fibroblast proliferation, confirming that LED light can be used as a substitute for the laser. Other in vitro studies have also found that light irradiation stimulates proliferation of different cell lines [14,[17][18][19].…”
Section: Introductionmentioning
confidence: 83%
“…Statistically significant difference (Wilcoxon, p<0.05) was observed between the two conditions However, although the mechanisms that guide the beneficial effects of LED light have been investigated in vitro, little is known about LED light transmission through the hard tissues of the body (e.g., bone, cartilage, enamel, dentin). Until now, several studies have referred only to the effects of light applied directly to different cell lines [14,[16][17][18][19]. It is important to obtain data about the effects of transdentinal illumination on the behavior of typical pulp cells because the light has to propagate through the dentin barrier to interact with the pulp cells during clinical application of phototherapy to reduce dental pain and/or accelerate tissue healing.…”
Section: Discussionmentioning
confidence: 99%
“…This inflammation is absolutely required to provide wound healing, although its long-term persistence is considered one of the most important reasons of delay in the healing process 12 . During the first days of healing, biological events such as formation of new capillary blood vessels associated with progressive deposition and remodeling of collagen fibers will culminate in a complete cicatricial repair of the injured area 13 .…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of red light on the skin have been suggested by many studies [35][36][37][38][39][40][41][42][43][44][45]. It has been demonstrated by an in vitro study that red light influenced cytokine release from macrophages, which consequently stimulated fibroblast proliferation [35].…”
Section: Discussionmentioning
confidence: 99%
“…A series of comprehensive studies performed by Whelan et al [43][44][45] demonstrated that 670 nm LED treatment upregulated tissue regeneration genes and accelerated wound closure. Their study also showed that the expression of genes coding cytokines and their receptors was downregulated after red LED treatment.…”
Section: Discussionmentioning
confidence: 99%